AB0183 THE ROLE OF THE PHOSPHOLIPASE LP-PLA2 ACTIVITY IN SJOGREN'S SYNDROME RELATED LYMPHOMAGENESIS: A NEW SERUM BIOMARKER?. (June 2019) - Kotsifaki, Eleni; Nezos, Adrianos; Psarrou, Anna; Garantziotis, Panayiotis; Koutsilieris, Michael; Mavragani, Clio
Abstract : Background: One of the major complications of primary Sjogren's syndrome (SS) is the development of B-cell non-Hodgkin's lymphoma (B-NHL). The contribution of tissue macrophages in the pathogenesis of B-NHL, based on previous histopathological studies, appears to be significant. Extracellular lipoprotein-associated phospholipase A2 (Lp-PLA2) is a product of tissue macrophages which is found in the circulation associated with lipoproteins and has been involved in both cardiovascular and malignant diseases, including B-NHL lymphoma. Objectives: The purpose of the current study was to investigate the role of serum Lp-PLA2 activity as a potential biomarker for the development of B-NHL in the setting of primary SS. Methods: Extracellular Lp-PLA2 activity was determined by measuring [ 3 H]PAF degradation products in liquid scintillation counter in serum samples obtained from 48 primary SS patients, 9 primary SS patients complicated by lymphoma (SS-lymphoma) and 40 healthy controls. Similar results were obtained in an independent cohort of 25 primary SS patients, 17 primary SS-lymphoma and 10 healthy controls, when a commercially available ELISA kit was implemented. Statistical analysis was performed with the Graph Pad software. Results: The activity of Lp-PLA2 was statistically significant increased in patients with primary SS-lymphoma compared to primary SS patients without lymphoma [mean±SD (nmol/min/ml): 62.0±13.4 vs 47.7±14.7, p=0.003 and 19.7±4.7 vs 15.2±3.2, p=0.005, respectively], as well as healthy controls [mean±SD (nmol/min/ml): 62.0±13.4 vs 52.0±16.3, p=0.03 and 19.7±4.7 vs 15.7±3.1, p=0.06, respectively]. No statistical significant differences in Lp-PLA2 activity were detected between primary SS patients without lymphoma development and healthy controls. Conclusion: Evaluation of extracellular Lp-PLA2 activity in primary SS patients could be a useful serological biomarker for B-NHL development in the context of primary SS. References: [1] Fragkioudaki S, Mavragani CP, Moutsopoulos HM. Predicting the risk for lymphoma development in Sjogren syndrome: An easy tool for clinical use. Medicine (Baltimore). 2016Jun;95(25):e3766. [2] Li D, Wei W, Ran X, Yu J, Li H, Zhao L, Zeng H, Cao Y, Zeng Z, Wan Z. Lipoprotein-associated phospholipase A2 and risks of coronary heart disease and ischemic stroke in the general population: A systematic review and meta-analysis. Clin Chim Acta. 2017Aug;471:38-45. [3] Markakis KP, Koropouli MK, Grammenou-Savvoglou S, van Winden EC, Dimitriou AA, Demopoulos CA, Tselepis AD, Kotsifaki EE. Implication of lipoprotein associated phospholipase A2 activity in oxLDL uptake by macrophages. J Lipid Res. 2010Aug;51(8):2191-201. [4] Lecointe N, Meerabux J, Ebihara M, Hill A, Young BD. Molecular analysis of an unstable genomic region at chromosome band 11q23 reveals a disruption of the gene encoding the alpha2 subunit of platelet-activating factor acetylhydrolase(Pafah1a2) in human lymphoma. Oncogene. 1999May6;18(18):2852-9. Disclosure of Interests: None declared